Primary health care principles for transgender individuals - Muzaffer Serdar Deniz; Didem Özdemir; Bekir Cakir (Ankara Medical Journal, 2021)
The sharp rise in gender diversity has led to an increased likelihood of general health workers encountering this group of patients. Awareness and approach of physicians working in primary health care about the sexual orientation and gender identity of the patients are important to provide a qualified and comprehensive health service. In this context, considering the health needs of transgender individuals and the problems they experience in accessing health services, the management of these people in primary care requires special attention. Primary, secondary and tertiary prevention services can be provided for trans men and trans women in primary health care. Ideally, a multidisciplinary approach including primary care physicians, psychiatrists, endocrinologists, and surgeons should be adopted for healthcare services for transgender people. The aim of this review is to determine the principles of the management of transgender people and the health services that should be provided to them using current guidelines and to assist physicians in providing primary healthcare services to these patients.